Penyelesaian Sengketa Pengembalian Dana Haji Perspektif Fatwa DSN-MUI Nomor: 29/DSN-MUI/VI/2002: Studi Putusan Nomor2346/Pdt.G/2021/PA.Mdn - Sri Rizki; Cahaya Permata (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Hajj bailout funds gave birth to various polemics, one of which is the return of Hajj funds in the event of Hajj cancellation as in case decision number: 2346/Pdt.G/2021/PA.Mdn. This research aims to find out the judge's legal basis in resolving the refund of Hajj funds and how the decision is reviewed from the DSN-MUI fatwa No: 29/DSN-MUI/VI/2002. This type of research is normative juridical with a statute approach and judicial case studies approach. The results showed that the legal basis of the judge in resolving this case was based on the Civil Code and the main consideration of the judge was the contract, according to the researcher the judge should not only consider the contract but other regulations related to the collection of ujrah in financing Hajj bailout funds such as the DSN-MUI fatwa No: 29/DSN-MUI/VI/2002. Dispute resolution carried out by the plaintiff through the religious court is in accordance with DSN-MUI fatwa No: 29/DSN-MUI/VI/2002 because in dispute resolution through a sharia arbitration body it must be agreed by the parties in writing, but in this decision the parties did not include it in the contract.